Evaluation of disinfectants in the domestic environment under 'in use' conditions. - Scott, E. (Cambridge University Press, 1984)
An 'in use' test was developed to investigate effectiveness of disinfectant application and of detergent of hot water cleaning at kitchen, bathroom and toilet sites in the domestic environment. Detergent and hot water cleaning produced no observable reduction in microbial contamination. Single and daily application tests demonstrated that hypochlorite and phenolic disinfectants can be used to produce substantial reductions in bacterial contamination in the home. Results indicate that maximum protection afforded by disinfection is relatively brief; 3-6 h after disinfection, contamination levels were only marginally less than those observed at pretreatment. Some suggestions are made for improvements in home hygiene.